Return to Sports and Subsequent Injury Rates After Revision Anterior Cruciate Ligament Reconstruction With Patellar Tendon Autograft. (June 2014) - Shelbourne, K. Donald; Benner, Rodney W.; Gray, Tinker
Background: The return-to-sport and reinjury rates are not well defined after revision anterior cruciate ligament (ACL) reconstruction. Hypothesis: School-age athletes would have a higher rate of return to sports and reinjury to either knee after revision ACL surgery compared with college or recreational athletes. Study Design: Cohort study; Level of evidence, 2. Methods: Patients were prospectively studied after revision ACL reconstruction with bone-patellar tendon-bone (BPTB) autograft. Participants were grouped by competitive sport levels of school age (mean age, 16.6 ± 0.9 years; n = 84), college (19.6 ± 1.2 years; n = 58), or recreational adult (27.6 ± 4.1 years; n = 117). An activity survey was used to determine the specific sport and sport level patients participated in before and after surgery. The International Knee Documentation Committee (IKDC) knee survey and Cincinnati Knee Rating System (CKRS) survey responses were also obtained. Results: The rate of return to the same sport at the same level was 62 of 84 school-age athletes (74%), 43 of 58 college athletes (74%), and 73 of 117 recreational athletes (62%) ( P = .1065). The number of patients who had a subsequent ACL graft tear rate after revision surgery was 2 of 84 (2.3%) in the high school group, 3 of 58 (5.1%) in the college group, and 4 of 117 (3.4%) in the recreational group ( P = .6706). The number of patients who had a subsequent ACL tear in the contralateral knee was 1 of 84 (1.1%) in the school-age group, 1 of 58 (1.7%) in the college group, and 2 of 117 (1.7%) in the recreational group ( P = .9501). At 2 years postoperatively, the mean IKDC subjective total score was 86.1 ± 11.7 points and the mean CKRS total score was 89.7 ± 11.1 points. Conclusion: Revision ACL reconstruction with BPTB autograft and perioperative rehabilitation allowed high school and college athletes to return to sports at the preinjury level at a rate of 74%; the return rate for recreational-level adults was 62%. Reinjury rates in the first 5 years after revision surgery ranged from 2% to 5%, which is lower than what has been reported for young competitive athletes after primary surgery.